Myocardial revascularization: factors intervening in the reference and counter-reference in Primary Health Care - Kamylla Santos da Cunha; Giovana Dorneles Callegaro Higashi; Alacoque Lorenzini Erdmann; Carolina Kahl; Cintia Koerich; Betina Hörner Schlindwein Meirelles
Abstract OBJECTIVE Understanding the factors that influence the reference and counter-reference process of people indicated/submitted to Myocardial Revascularization surgery in the Primary Health Care scenario. METHOD A qualitative research anchored in the Grounded Theory, totaling 41 participants subdivided into three groups (patients, health professionals and managers) in the Metropolitan and West Region of Santa Catarina. RESULTS Two categories elucidate the intervening factors found, contrasting the potentialities and obstacles in (creating) the bond between people affected by cardiovascular diseases and primary health care for the reference process, highlighting weaknesses in the primary health care services provided, with failures in the counter-reference for people submitted to myocardial revascularization surgery. CONCLUSION Strengthening the potentialities presented in this study is essential for the reference process of people affected by Cardiovascular Disease, as well as strategic actions focused on solving the evidenced obstacles which contribute to deficiencies in the referral and counter-referral process, thus impeding integral care in the health care network.